2001
DOI: 10.1590/s0102-311x2001000500015
|View full text |Cite
|
Sign up to set email alerts
|

Detecção de aglomerados espaciais de óbitos por causas violentas em Porto Alegre, Rio Grande do Sul, Brasil, 1996

Abstract: Violence is of major importance in the health profile of Brazilian metropolitan areas and should be treated as a public health problem. Spatial analysis methods can be highly useful for the surveillance and prevention of violence. This paper analyzes the spatial distribution of victims' place of residence in relation to the main causes of violent death in Porto Alegre (1996)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
25

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 9 publications
(5 reference statements)
2
23
1
25
Order By: Relevance
“…A paradoxical inverse relationship was found contrasting with studies that found an association between poverty and femicides 9,12 or poverty and homicides. 2,15,22 Since the economic variables were strongly interrelated showing high colinearity and potential confounding effects they were not included in the multivariate analysis model.…”
Section: Discussionmentioning
confidence: 99%
“…A paradoxical inverse relationship was found contrasting with studies that found an association between poverty and femicides 9,12 or poverty and homicides. 2,15,22 Since the economic variables were strongly interrelated showing high colinearity and potential confounding effects they were not included in the multivariate analysis model.…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo epidemiológico no RS apontou o enforcamento como responsável por 62% das mortes em geral 6 . Dessa maneira, vemos que no extremo oeste de SC o enforcamento é o método significativamente mais usado para o suicídio, enquanto que outras formas, como armas de fogo e envenenamento, apresentam participação discreta, quando comparada a estudos já publicados; no RS, as armas de fogo são responsáveis por mais de 20% dos suicídios 6 , enquanto a média brasileira se situa em 25% 19 ; o envenenamento apresentou taxas de 31% em estudo no município de Ribeirão Preto 20 . Este é outro ponto que ainda carece de estudos mais detalhados.…”
Section: Discussionunclassified
“…The geographical information system (GIS) has contributed for more effective policy formulation for multisectoral intervention through analyses of spatial data in health. 17,18,23 Thus, the objective of the present study was to analyze the socioeconomic background and its relationship with spatial distribution of mortality due to homicide, suicide and traffi c accident.…”
Section: Introductionmentioning
confidence: 99%